Diagnostic and management problems of chylous effusion in a patient with newly-diagnosed tuberculosis - Dicky Febrianto; Usman Hadi (Universitas Airlangga, 2021)
Tuberculosis (TB) remains a major cause of morbidity and mortality globally. Although TB most commonly affects the lungs, any organ or tissue can be involved. Extra-pulmonary forms of TB are commonly unrecognized or late diagnosed. Chylous effusion, i.e. chylothorax and chylous ascites, which is characterized by the presence of chyle in the pleural and peritoneal cavities, is an uncommon manifestation of extra-pulmonary TB. A 22-year-old male, referred to Dr. Soetomo Hospital with complaints of dyspnea, fever, and abdominal distension. Chest X-ray showed pleural effusion. Analysis of fluid obtained from thoracentesis and paracentesis showed chylothorax and chylous ascites. M. tuberculosis had been found in sputum smear examination. ADA (adenosine deaminase) test was performed on ascites fluid and a positive result was obtained. Chylous effusion in this patient were concluded to be related to TB. Patient was then treated with anti-TB drugs and somatostatin. Chylothorax and chylous ascites improved after treatment with somatostatin for 1 week. Administration of anti-TB drugs was planned to be continued for 9 months. The most common causes of non-traumatic chylous effusion in developing countries are infection of TB and filariasis. Chylous effusion is caused by obstruction or disruption of the lymphatic system. ADA test is a new biomedical method that begins to expand its use in body fluids to diagnose extra-pulmonary TB. Fasting, together with total parenteral nutrition, can decrease the lymph flow and balance metabolic impairment. Somatostatin has been used in the treatment of chylous effusion as it diminishes peristalsis and intestinal absorption of fats as well as decreases portal pressure.